Development of a decision support system for the study of an area after the occurrence of forest fire. (9th February 2011) - Ioannou, Konstantinos; Lefakis, Panagiotis; Arabatzis, Garyfallos
There is a great diffusion of modern information systems in all areas of science. In the case of forestry, new information tools have emerged during the last 15 years which have helped to improve the work of foresters. Decision support systems (DSSs) are applications which are designed to help managers in the task of decision making, by accelerating the relevant decision-making processes, while simultaneously focusing on the conservation of natural, financial and human resources. In this paper, we describe the development of a DSS which has been designed to help managers in the process of decision making, in relation to areas that have been burnt by forest fires. In addition, the above system also provides the user with the capacity to create hypothetical (what-if) scenarios in order to achieve the best form of intervention. The relevant software was created using Visual C# and the weights of the various parameters were calculated using multi-criteria decision analysis.